The profile of the rare earth elements in the Canada Basin, Arctic Ocean. (12th August 2016) - Yang, Jon; Haley, Brian
Abstract: We analyzed the dissolved rare earth element (REE) content of three water column profiles (two shelf sites and one deep basin site) in the Canada Basin in order to better constrain the behavior of REEs in the Arctic Ocean. Dissolved concentrations of the REEs in the surface are 1.3–1.9 times higher than deep water (>500 m) concentrations, which are constant with depth (La: 19–23 pM, Nd: 14–17 pM, Yb: 4.0–4.3 pM). The dominant source of REEs to the surface waters of the Canada Basin is most likely Pacific water flowing through the Bering Strait and Chukchi Sea and/or the Mackenzie River. Dissolved REEs in the intermediate and deep waters are constant and appear to behave conservatively, allowing us to investigate this aspect of REE behavior in the oceans. Calculated deep ocean residence times of the REEs in the Canada Basin range from 450 to 700 years and match the age of these waters. We postulate that these values are likely applicable to global deep ocean reservoirs and that observed deviations from this conservative value can help to constrain nonconservative processes acting on the REEs. Key Points: Dissolved REE profiles in the Canada Basin are elevated in surface waters and invariant in deeper layers Localized inputs from Pacific inflow over the Chukchi Sea and Mackenzie River water provide REEs to the Canada Basin surface REEs in the deep Canada Basin behave conservatively and have estimated "preformed" residence times from 450 to 700 years